(untitled) (Research, Society and Development, 2022)
Aim of this study was to investigate the influence of the two methods of grafting on Passiflora gibertti in this antioxidant capacity. Experiment was conducted under field conditions in two agricultural years 2012/2013 and 2013/2014 following a randomized block design, being studied three treatments, plants not grafted, grafted plants by cleft grafting and grafted plants laterally and with maintenance of the root system. Fruit were harvested when they were physiologically ripe and taken to the laboratory for juice extraction and antioxidant compounds analysis. Total phenolic compounds, ascorbic acid, total flavonoids, Xanthoids contents and total antioxidant activity (DPPH) were evaluated. The use of two root systems showed higher contents of total phenolic compounds, flavonoids and ascorbic acid, however, had the total xanthoids contents decreased. It is concluded that the technique of grafting with the use of two root systems is favorable to the accumulation of higher levels of antioxidants.